2007
DOI: 10.1143/jjap.46.5193
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Fluorescent Poly(methyl methacrylate) Beads Hybridized with Y3Al5O12:Ce3+ Nanophosphor for Biological Application

Abstract: Poly(methyl methacrylate) beads were hybridized with Y 3 Al 5 O 12 :Ce 3þ nanoparticles through electrostatic interactions using the layer-by-layer adsorption technique to prepare fluorescent beads for biological application. The subsequent sequential adsorption of poly(sodium 4-styrenesulfonate) and poly(allylamine hydrochloride) onto the composite beads prevented the detachment of the Y 3 Al 5 O 12 :Ce 3þ nanoparticles. The fluorescent beads were observed as tight dot plots by flowcytometry. Bovine serum alb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…15 We previously reported that the YAG: Ce 3+ nanoparticles can be used for biological application. 16,17 In this work, we produce the transparent color conversion thick film which is composed of a high concentration of YAG: Ce 3+ nanoparticles prepared by glycothermal method, and characterize its optical properties.…”
mentioning
confidence: 99%
“…15 We previously reported that the YAG: Ce 3+ nanoparticles can be used for biological application. 16,17 In this work, we produce the transparent color conversion thick film which is composed of a high concentration of YAG: Ce 3+ nanoparticles prepared by glycothermal method, and characterize its optical properties.…”
mentioning
confidence: 99%
“…In this technique, two different types of materials with opposite charges can be easily combined through electrostatic interaction for a short reaction time [5]. The LbL technique has been applied to the formation of composite beads hybridized with fluorescent nanoparticles such as quantum dots [6] and Y 3 Al 5 O 12 :Ce 3+ [7]. Here we report the preparation of composite PMMA beads hybridized with fluorescent YVO 4 :Bi 3+ ,Eu 3+ nanoparticles using the LbL adsorption technique.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Moreover, functionalizing the external surface of the these fluorescent nanoparticles and embedding them into a dielectric ͑e.g., polymer͒ matrix has enabled the realization of a large variety of novel optophotonic devices. [9][10][11][12][13][14] Recently, due to the wealth of existing organic fluorescent dyes, their encapsulation into either an inorganic or an organic host has been demonstrated to be a very promising and versatile approach to synthesize a large palette of new fluorescent pigments.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, both organic-inorganic [14][15][16] and organic-organic [17][18][19] host-guest nanosystems have been extensively developed for the chemical, photochemical or thermal stabilization and the supramolecular organization of organic fluorescent dye molecules, complexes, and clusters. [19][20][21][22][23][24][25] The most common examples of such systems are ͑i͒ nanoporous zeolites: besides their widespread commercial use as catalysts and ion-exchangers, 26 due to their nanoporous framework consisting of nanochannels with a minimal diameter of several angstrom, they have been used as inorganic hosts for the encapsulation of different organic molecules, 2,20-22,27-31 ͑ii͒ mesoporous silica particles: because of their uniform porosity, they have been recently proposed as promising inorganic hosts with an adjustable pore size in the range of 1-10 nm, 32-35 ͑iii͒ silica nanoparticles: once loaded with fluorescent organic dyes, these inorganic nanohosts have been shown to possess interesting physical-chemical and photochemical properties, [36][37][38][39][40] ͑iv͒ fluorescent polymer nanoparticles: as stable organic hosts, they have attracted both research 6,8,[17][18][19]23,25,41 and commercial 42 interest for the development and the fabrication of novel functional materials; ͑v͒ organic-organic supramolecular complexes: they have been developed using organic macromolecules as hosts that can encapsulate small organic molecules or ions. 43,44 Due to their high versatility, these host-guest systems offer a wide range of possibilities for preparing nanopigments with tailored chemical and physical properties.…”
Section: Introductionmentioning
confidence: 99%